KZ Characteristic Variety as the Zero Set of Classical Calogero-Moser Hamiltonians - Mukhin, E.; Tarasov, T.; Varchenko, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
We discuss a relation between the characteristic variety of the KZ equations and the zero set of the classical Calogero-Moser Hamiltonians.